DECISION MAKING FOR SELECTION OF EMERGENCY ENERGY SUPPLY FOR MASS RAPID TRANSPORT SYSTEM USING ANALYTIC HIERARCHY PROCESS - Darajatun, Rifkiandi
PT MRT Jakarta is the first company providing mass rapid transport services to support people's mobility and economic growth in Jakarta City. The current MRT Phase 1 Operation consists of an integrated system of railway infrastructure with train sets, elevated and underground stations, depot buildings, power distribution, and signaling systems. In the year 2019, PT MRT Jakarta had the targets for the average number of passengers of 65,000 per day and succeeded in exceeding the average daily number of passengers at 89,645 passengers per day with a performance of service is 99.88% on time. The excellent performance of MRT Operation had been disrupted by an event of total blackout of PLN power supply that caused four operating trains were automatically stopping in-between stations and it required the emergency evacuation of total of 3,410 passengers. This incident had left a business issue concerning the reliability of the energy supply to MRT system operation. The situation analysis and problem analysis on the energy supply system for train system operation is elaborated using the Rational Management methodology of Kepner-Tregoe. The analysis of the situation and problem in the existing electricity supply system provides confirmation that the root cause of the problem is DC Traction System which has a high dependency on the main supply line from PLN feeders. Although there is a provision of a redundant supply system by two (2) incoming 150kV PLN feeder lines, it does not constitute a guarantee of continuous energy supply availability in the event of PLN power outage. Reliable energy supply to 1500V DC Traction System is required to allow coasting of the train to the nearest station for emergency conditions. The Analytic Hierarchy Process elaborates on the decision-making process to define and select the alternative options for the emergency energy supply to DC Traction Systems. Four (4) criteria and twelve (12) sub-criteria are defined to select the alternative options for emergency energy supply. Results of AHP calculation shows three (3) criteria as the main contributor to overall weight are Safety Health Environment (0.382), Budget Availability (0.283), Operational Efficiency (0.233) and sub-criteria with highest global priority are Cost of operation and maintenance (0.197), Risk to the operation and maintenance team at the site (0.179) and Operability & Maintainability (0.111). Based on those criteria and sub-criteria, three (3) alternative options for problem solution are developed: Additional Diesel Engine Generator, Provision of Gas Engine Generator and Battery Energy Storage Systems. Priority calculation of alternatives is conducted from the pairwise comparison between qualitative sub-criteria and the normalized value of quantitative measurement for quantitative sub-criteria. Selecting the alternative options is done using the two matrices by multiplication of Combined priority calculation for all respondents and Priority calculation of alternatives, with the result of Option B (Provision of Gas Engine Generator) as the best proposal with its highest final priority of 0.3897 (38.97%). The highest priority of the sub-criteria is under SHE criteria: Potential risk to the environment (0.535/53.5%), Potential risk to the community (0.460/46.0%), Potential risk to the site team (0.458/45.8%).